First-pass success in video laryngoscopy with transcutaneous infrared illumination in patients with normal airways–a clinical pilot study - Abdulrahman Dardeer (15900223) (2025)
Purpose Endotracheal intubation is a critical skill in anesthesia, particularly for patients with compromised airways. This randomized pilot study evaluated the feasibility and impact of the Infrared Red Intubation System (IRRIS®) on video laryngoscopy performance, first-attempt success rate, and intubation time. Methods Thirty patients were randomized into two groups: one with the IRRIS device and one without (control). The primary outcome was the impact of IRRIS on first-pass success. Secondary outcomes included glottic visibility, intubation time, and adverse effects. Results Results showed that both groups demonstrated nearly identical percentages of glottic opening (POGO) and glottic entrance visibility, achieving successful intubation on the first attempt. Although the IRRIS group had a slightly longer intubation time and more instances of required external manipulation, the vocal cords were not visible without IRRIS in the most obese patient in our cohort. Conclusion The IRRIS device effectively illuminated the laryngeal inlet, enhancing differentiation from surrounding structures, such as the esophagus. This study suggests that IRRIS may be a valuable adjunct for video laryngoscopy in patients with difficult airways, though further research is needed to assess its broader applicability. Background Endotracheal intubation in patients with compromised airways is a notoriously complex and daunting task for anesthesiologists. Throughout the years, numerous supportive techniques and innovative equipment have been developed to address this challenge. This randomized clinical study sheds light on the potential benefits of utilizing an external pre-cricoid emitting infrared light source, the ‘Infrared Red Retrograde Intubation System’ (IRRIS®), which produces a flashing light that can be detected within the airway. By leveraging this technology, anesthesiologists may be able to identify the airway quicker and more accurately, both in terms of time and anatomical level, compared to relying solely on a video laryngoscope/ flexible bronchoscope. Other Information Published in: Journal of Clinical Monitoring and Computing License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1007/s10877-025-01361-4